CALCULATION OF THE STANDARD MOLAL THERMODYNAMIC PROPERTIES OF CRYSTALLINE, LIQUID, AND GAS ORGANIC MOLECULES AT HIGH TEMPERATURES AND PRESSURES - Helgeson H.C.; Owens C.E.; Knox A.M.; Richard L. (My University, 1998)
Calculation of the thermodynamic properties of organic solids, liquids, and gases at high temperatures and pressures is a requisite for characterizing hydrothermal metastable equilibrium states involving these species and quantifying the chemical affinities of irreversible reactions of organic molecules in natural gas, crude oil, kerogen, and coal with minerals and organic, inorganic, and biomolecular aqueous species in interstitial waters in sedimentary basins. To facilitate calculations of this kind, coefficients for the Parameters From Group Contributions (PFGC) equation of state have been compiled for a variety of groups in organic liquids and gases. In addition, molecular weights, critical temperatures and pressures, densities at 25°C and 1 bar, transition, melting, and boiling temperatures (Tt,Pr, Tm,Pr, and Tv,Pr, respectively) and standard molal enthalpies of transition (ΔH°t,Pr), melting (ΔH°m,Pr), and vaporization (ΔH°v,Pr) of organic species at 1 bar (Pr) have been tabulated, together with an internally consistent and comprehensive set of standard molal Gibbs free energies and enthalpies of formation from the elements in their stable state at 298.15 K (Tr) and Pr (ΔG°f and ΔH°f, respectively). The critical compilation also includes standard molal entropies (S°) and volumes (V°) at Tr and Pr, and standard molal heat capacity power function coefficients to compute the standard molal thermodynamic properties of organic solids, liquids, and gases as a function of temperature at 1 bar. These properties and coefficients have been tabulated for more than 500 crystalline solids, liquids, and gases, and those for many more can be computed from the equations of state group additivity algorithms. The crystalline species correspond to normal alkanes (CnH2(n+1)) with carbon numbers (n, which is equal to the number of moles of carbon atoms in one mole of the species) ranging from 5 to 100, and 23 amino acids including glycine (C2H5NO2), alanine (C3H7NO2), valine (C5H11NO2), leucine (C6H13NO2), isoleucine (C6H13NO2), aspartic acid (C4H7NO4), glutamic acid (C5H9NO4), asparagine (C4H8N2O3), glutamine (C5H10N2O3), proline (C5H9NO2), phenylalanine (C9H11NO2), tryptophan (C11H12N2O2), methionine (C5H11SNO2), serine (C3H7NO3), threonine (C4H9NO3), cysteine (C3H7SNO2), tyrosine (C9H11NO3), lysine (C6H14N2O2), lysine:HCl (C6H15N2O2Cl), arginine (C6H14N4O2), arginine:HCl (C6H15N4O2Cl), histidine (C6H9N3O2), and histidine:HCl (C6H10N3O2Cl).Unless indicated otherwise, all amino acid designations in the present communication refer to the L-α form.